PENGGUNAAN NEW MEDIA DI KALANGAN IBU MUDA SEBAGAI MEDIA PARENTING MASA KINI - Ascharisa Mettasatya Afrilia (Jurnal Komunikasi dan Kajian Media, 2017)
Parenting among young mothers has slipped off from offline to online activities. This is related to the development of information technology, exposing the social reality by new kinds of media. One of these new media derivatives is social media which was considered superior in the speed of distributing messages. More so, social media is also considered as a special space to share parenting experiences among young mothers. Research showed that social media which later became the "public space", has in fact been regarded as a more credible medium for discussion, exchanging experience, and some even use it as a contemporary label in order to maintain prestige. It is the result of two general motives which in this study referred to as rational motives and emotional motives.